2016
DOI: 10.1038/srep19696
|View full text |Cite
|
Sign up to set email alerts
|

All-photonic drying and sintering process via flash white light combined with deep-UV and near-infrared irradiation for highly conductive copper nano-ink

Abstract: We developed an ultra-high speed photonic sintering method involving flash white light (FWL) combined with near infrared (NIR) and deep UV light irradiation to produce highly conductive copper nano-ink film. Flash white light irradiation energy and the power of NIR/deep UV were optimized to obtain high conductivity Cu films. Several microscopic and spectroscopic characterization techniques such as scanning electron microscopy (SEM), a x-ray diffraction (XRD), and Fourier-transform infrared (FT-IR) spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 42 publications
0
57
0
Order By: Relevance
“…As shown in Supplementary Fig. S9 , the DSC curves of Sn and mixed Cu/Sn ink presented the endothermic peak around 230 °C while it did not exist in the Cu ink, which means that the Cu metal-mesh TCF has higher instantaneous temperature than Cu/Sn metal-mesh TCF under the same condition, causing unreleased massive stress 32 , 34 37 . On the other hand, the melting of Sn particles around Cu particles played the role of releasing part of stress caused by momentary temperature.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Supplementary Fig. S9 , the DSC curves of Sn and mixed Cu/Sn ink presented the endothermic peak around 230 °C while it did not exist in the Cu ink, which means that the Cu metal-mesh TCF has higher instantaneous temperature than Cu/Sn metal-mesh TCF under the same condition, causing unreleased massive stress 32 , 34 37 . On the other hand, the melting of Sn particles around Cu particles played the role of releasing part of stress caused by momentary temperature.…”
Section: Resultsmentioning
confidence: 97%
“…33 Hwang et al reported that deep-UV sintering can result in dense packing of the printed nanoparticles. 34 When the same nanoparticle colloid was printed using Ar/H 2 plasma, it showed a significant rise in conductivity. Although the resistance is of the order of 140 Ω, the rise in conductivity is indicative of the fact that the in situ process can be used to create conductive patterns from rather insulating ink.…”
Section: Resultsmentioning
confidence: 99%
“…Testing or characterization validates the initial design. Adapted with permission from [9,[14][15][16][17][18][19][20]. 2 International Journal of Antennas and Propagation approaches.…”
Section: Challenges Aheadmentioning
confidence: 99%